The road to peace: exploring the economic programs of counterinsurgency strategy as a method to achieve peace in areas of armed internal conflict - Davis, Jason Cameron Mcmichael (2018)
This article uses the counterinsurgency framework of Nathan Leites and Charles Wolf, Jr. to analyze a case study of Plan Colombia from 2000-2011. In particular, it studies the impacts of Plan Colombia-funded economic programs and their relationship to violence in the Colombian conflict. Previous academic works have looked at efficacy of counter-insurgency and the impacts of strategies from a \"hearts and minds\" approach, while this article attempts to look at the efficacy from a systemic approach. This systemic approach views insurgencies as a system that requires inputs, conversion of these inputs and the outputs or activities. Leites and Wolf further highlight that this capacity is incumbent upon: 1) the government\'s adherence to law and order in contrast to the insurgency and 2) its ability to demonstrate that it can govern and complete programs and activities. With this theoretical framework, there is also an assumption that increases in government effectiveness and control increase legitimacy in said areas and thus blunt insurgent activities. Thus, in order to relate this framework, this research uses a logical approach by linking the Leites and Wolf framework to the concepts laid out by Galula regarding counterinsurgency and the importance of the populace. This article studies the trend between the change in economic values and the change in insurgent activity. This research does not try to show a causal relationship between the two datasets, but only that there is a relationship between the increase in economic indicators and a decrease in events and attacks that can be associated the overall effects of the two economic programs. This article suggests that there is an inconclusive relationship and although there is drop in insurgency attacks and events, more research is necessary to ascertain the actual correlation between the effect of economic programs on insurgency attacks and events.